Analytical and Hybrid Methods in the Theory of Slot-Hole Coupling of Electrodynamic Volumes - Katrich, Victor A.; Penkin, Yuriy M.; Berdnik, Sergey L. (Springer New York : Imprint: Springer, 2008)
Analytical and Hybrid Methods in the Theory of Slot-hole Coupling of Electrodynamic Volumes arose from the original research results, never before published, first obtained by the authors at Karazin Kharkov National University, Ukraine. Impetuous development of technical opportunities of PC for the last twenty years, and a powerful set of numerical methods available in the arsenals of investigators have forced the working-outs connected with the search of analytical solutions of radiophysical problems backward. However, at present, the fact is evident that optimal use of computer calculations should be based on application of analytical methods of boundary problems solution. These methods allow to increase PC use efficiency and also expand their calculation abilities to solve complex electrodynamic problems. The authors' experience in the development of analytical methods to solve the problems of diffraction of waveguide electromagnetic waves on slot coupling holes serves as a useful tool to readers interested in both the field of theoretical electrodynamics and the field of practical workings-out of multi-functional waveguide devices and systems using slot-coupling elements. Topics covered in this book are: problem formulation and initial integral equations the averaging method analytical solution of the integral equations for a current induced magnetomotive forces method for analysis of coupling slots in waveguides resonant iris with the slot arbitrary oriented in a rectangular waveguide stepped junction of the two rectangular waveguides with the impedance slotted iris This book is intended for academic and industrial researchers involved in Microwave Techniques, as well as advanced students studying Radiophysics and Applied Electrodynamics.